Acceptance and commitment training: A review of the research. Issue 2 (3rd July 2021) - Cihon, Joseph H.; Ferguson, Julia, L.; Leaf, Justin B.; Milne, Christine M.; Leaf, Ronald; McEachin, John
ABSTRACT: There have been recent efforts forusing Acceptance and Commitment Training (ACTraining) to distinguish between Acceptance and Commitment Therapy (ACT) when applied in psychotherapeutic or counseling settings and ACTraining when applied within the scope of practice of Board Certified Behavior Analysts.Despite these efforts, identifying methodological and/or procedural differences within the literature is difficult. If differences exist, it may be useful to evaluate research that has explicitly evaluated the effectiveness of ACTraining. The purpose of this paper is to provide an analysis of studies that have evaluated the effectiveness of ACTraining using standards for quality indicators of experimental control, operational definitions of the independent and dependent variables, monitoring of treatment integrity, and risk for treatment inaccuracies. Results indicated the majority of studies lacked convincing evidence of experimental control, could not be replicated with the information provided, failed to collect treatment integrity data, and were at high risk for treatment inaccuracies.